2018
DOI: 10.1097/ftd.0000000000000506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cytochrome P450 (CYP) 2C19 Genotypes on Steady-State Plasma Concentrations of Escitalopram and its Desmethyl Metabolite in Japanese Patients With Depression

Abstract: Background:Plasma concentrations of the S-enantiomer of citalopram were different between extensive and poor CYP2C19 metabolizers in healthy subjects and depressed patients. However, most studies applied dose-corrected concentrations. Thus, we studied the effects of polymorphisms of the CYP2C19 gene on raw plasma drug concentrations in Japanese patients with depression.Methods:Subjects in this study consisted of 412 depressed patients receiving 5, 10, 15, or 20 mg of escitalopram once a day. Plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…Six studies showed an association between ESC BL and CYP2C19 metabolism ( 25 29 , 32 ). Four studies showed an increase in ESC BL (dose-corrected and non-dose-corrected) of up to 90% and 470% in patients carrying heterozygous and homozygous non-functioning CYP2C19 alleles (either *2, *3, or *4 alleles), respectively ( 25 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies showed an association between ESC BL and CYP2C19 metabolism ( 25 29 , 32 ). Four studies showed an increase in ESC BL (dose-corrected and non-dose-corrected) of up to 90% and 470% in patients carrying heterozygous and homozygous non-functioning CYP2C19 alleles (either *2, *3, or *4 alleles), respectively ( 25 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies examined the effect of age on ESC BL ( 21 23 , 29 , 31 , 32 ), four of which found an association ( 21 , 22 , 29 , 32 ), while two did not ( 23 , 31 ). In one study, older age correlated with higher ESC dose-normalized BL ( 22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study has some limitations that need to be recognized. First, the sample size is smaller than previously SSRI studies published 35,36 ; nevertheless, considering the outpatient condition of the patients included, the sample size resulted adequate compared to similar antidepressants studies 13,37 . Second, the outpatient setting condition did not guarantee medication adherence due to the unsupervised administration of the drugs and there is knowledge that factors like difficulty in accepting the need for long‐term treatment and preference for the psychological management, make frequent high non‐adherence rates in psychiatric clinical practice 38 .…”
Section: Discussionmentioning
confidence: 97%